Building a "Special Didactics" of Engineering Subjects: Its Need and Solution - Nguyen , Thị Hương Giang; Pham, Hồng Hạnh (Journal of Technical Education Science, 2008)
The paper refers to the need and solution of building a Special Didactics for training and improving instructional skills of the teaching staff in the technical and vocational schools.